Factors affecting the technical efficiency of general hospitals in Iran: data envelopment analysis. Issue 1 (March 2016) - Kalhor, Rohollah; Amini, Saeed; Sokhanvar, Mobin; Lotfi, Farhad; Sharifi, Marziye; Kakemam, Edris
Abstract : Background: Restrictions on resource accessibility and its optimal application is the main challenge in organizations nowadays. The aim of this research was to study the technical efficiency and its related factors in Tehran general hospitals. Materials and methods: This descriptive analytical study was conducted retrospectively in 2014. Fifty-four hospitals with private, university, and social security ownerships from the total 110 general hospitals were randomly selected for inclusion into this study on the basis of the share of ownership. Data were collected using a checklist with three sections, including background variables, inputs, and outputs. Results: Seventeen (31.48%) hospitals had an efficiency score of 1 (highest efficiency score). The highest average efficiency score was in social security hospitals (84.32). Private and university hospitals ranked next with an average of 84.29 and 79.64, respectively. Analytical results showed that there was a significant relationship between hospital ownership, hospital type in terms of duty and specialization, educational field of the chief executive officer, and technical efficiency. There was no significant relationship between education level of hospital manager and technical efficiency. Conclusion and recommendations: Most of the studied hospitals were operating at low efficiency. Therefore, policymakers should plan to improve the hospital operations and promote hospitals to an optimal level of efficiency.